2012
DOI: 10.5625/lar.2012.28.3.193
|View full text |Cite
|
Sign up to set email alerts
|

Anticoccidial effects ofGalla rhoisextract onEimeria tenella-infected chicken

Abstract: Anticoccidial effects of Galla rhois (GR) extract were evaluated in chickens after oral infection with Eimeria tenella. This study was performed using 3-day-old chickens (n=30). The animals were divided into 3 groups as follows: GR 0.5%/infected (n=10), untreated/infected (n=10), and non-infected control (n=10). The chickens were fed a standard diet supplemented with or without GR for 1 week before infection with E. tenella (10,000 sporulated oocysts per chicken). The effects of GR on E. tenella infection were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…Gallarhois (GR) is a traditional oriental drug used to treat diarrhea, persistent coughing and spontaneous perspiration, although there is little scientific evidence supporting these pharmacological effects in humans. Recently, several studies revealed that tannin-derived components of GR effectively inhibit bacteria, fungi and viruses 30, 31. In addition, methyl gallate and ethyl gallate isolated from GR also showed significant anti-inflammatory activity in lipopolysaccharide (LPS)-stimulated RAW264.7 macrophages via induction of hemoxic enzyme 1 and inhibition of iNOS/COX-2 22, 32.…”
Section: Discussionmentioning
confidence: 99%
“…Gallarhois (GR) is a traditional oriental drug used to treat diarrhea, persistent coughing and spontaneous perspiration, although there is little scientific evidence supporting these pharmacological effects in humans. Recently, several studies revealed that tannin-derived components of GR effectively inhibit bacteria, fungi and viruses 30, 31. In addition, methyl gallate and ethyl gallate isolated from GR also showed significant anti-inflammatory activity in lipopolysaccharide (LPS)-stimulated RAW264.7 macrophages via induction of hemoxic enzyme 1 and inhibition of iNOS/COX-2 22, 32.…”
Section: Discussionmentioning
confidence: 99%
“…After the confirmation of the parasite species, oocysts were collected, sporulated, and washed, and the dose was adjusted to 4 × 10 4 /100 μL/bird. At 21 d of age, all the birds, except for group 5, were orally gavaged with a 1 mL suspension of distilled water containing 40,000 E. tenella sporulated oocysts ( Lee et al., 2012 ).…”
Section: Methodsmentioning
confidence: 99%
“…Oocysts were then collected, sporulated, washed, and adjusted to 1 × 10 4 /100 µL/bird. A total of 10,000 sporulated oocysts were administered orally (gavage) to each experimental chicken in 1 mL of distilled water [ 40 ].…”
Section: Methodsmentioning
confidence: 99%